Floristic and phytosociological study of an urban fragment of secondary Amazonian forest in Capitão Poço – PA - Sales, Denyse Cássia de Maria; Luz, Ana Laura da Silva; Rodrigues, Nívea Maria Mafra; Oliveira, Wendel Kaian Mendonça; Silva, Raimundo Thiago Lima da; Carvalho, João Olegário Pereira de (Revista de Ciências Agroveterinárias, 2023)
Secondary forests constitute important regenerating areas and they are expanding rapidly in the Amazonian landscape. The characterization of forest remnants provides essential information for conservation, management and recovery actions. The objective of the present study was to conduct a floristic and phytosociological evaluation of an urban fragment of secondary Amazonian forest (8.12 ha) in Capitão Poço, Pará. Trees with DBH ≥ 3.2 cm were inventoried in five 15 m x 30 m plots. The floristic diversity, importance value, and diametric distribution were investigated. In the survey, 236 individuals from 23 species were recorded. The floristic diversity index was 2.58. The most important species were Cecropia obtusa Trécul and Lacistema pubescens Mart. The curve of distribution of individuals in diametric classes followed a negative exponential pattern (inverted J-shape), with most individuals in the smallest diametric classes. These results imply that the forest presents species typical of initial stages of succession. Thus, conservation actions are needed to increase the local diversity. In addition, the studied forest is essential for academic and environmental education activities. We recommend further floristic studies in the area in order to assess the dynamics of the species in the forest community.